ANALISIS EFEKTIVITAS PROGRAM INOVASI DESA BERBASIS MASYARAKAT DI KABUPATEN SERANG - Ayang Gusti Mulia (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
The village innovation program is here to increase community productivity and economic independence and is ready to build competitive resources. This articile aims, i.e: 1) to identify the process of developing the village innovation program in the three villages of Serang district, 2) to analyze the effectiveness of the existing village innovation program in Serang district, and 3) to determine the process of developing the Village Innovation Program Desa Innovation in three villages in Serang district. The collection of data and information sources is carried out using primary and secondary methods. Qualitative collection is carried out through Focus Group Discussion (FGD) techniques, and in-depth interviews, especially to parties or actors who are directly involved in the Village Innovation Program (Program Inovasi Desa/PID), FGD and in-depth interviews were conducted with several members who had long been members of the farmer groups. Likewise, the role of village local assistants is important in assisting the community in carrying out this program in order to prosper the community's economy. The results of this study state that the implementation of the Village Innovation Program for the community explains that the priority of farmer groups in this village innovation program will increase the market scale with a weight of 0.27 and market scale results with a weight of 0.26, and the Consistency Index (CI) of 0.04 with Consistency Ratio (CR) 0.90, this states that farmer groups prioritize market scale results.